Implementasi Program Literasi dan Numerasi Melalui KKN Rekognisi di Yayasan Kanker Anak Sumatera Selatan - Rio Erlando; Titin Hartini (Jurnal Aksi Dosen dan Mahasiswa, 2025)
This study aims to analyze the implementation and impact of literacy and numeracy programs through the Community Service Recognition Program on the educational development of childhood cancer survivors. This study employed a qualitative approach with participatory methods through the KKN Rekognisi program for 1 months (April-May 2025) at the South Sumatra Children's Cancer Foundation. The program included home schooling, hospital schooling, social service activities, and information dissemination with a total of 180 activity hours. There was a significant improvement in children's literacy and numeracy abilities, where 80% of children were able to recite the alphabet, 75% could read simple words, 70% could write their names and short words, and 85% could recite numbers 1-10. Active participation of children increased from baseline conditions to more than 80%. The literacy and numeracy program through a learning-through-play approach proved effective in improving the academic and non-academic abilities of childhood cancer survivors, as well as providing positive impacts on their self-confidence and spirit of life.